Accept No Substitutes: The Ethics of Alternatives - Marks, Joel (The Hastings Center report, 2012)
It is common to argue that animal experimentation is justified by its essential contribution to the advancement of medical science. But note that this argument actually contains two premises: an empirical claim that animal experimentation is essential to the advancement of medical science and an ethical claim that if research is essential to the advancement of medical science, then it is justified. Neither premise looks weak; the first premise is an article of faith for most biomedical researchers, and the second is usually considered so obviously true that it goes unstated. In fact, however, both are open to challenge. In the logic of the case, only one of the premises needs to be shown false or moot in order to refute the argument. A number of other commentators have questioned the first, but it is the ethical premise that I find particularly wanting.